On the hunt - Johansen, Iris (Johansen, Iris. Kira Drake series, 2024)
"Kira Drake has come to Paris with her highly trained golden retriever Mack to investigate the horrific bombing of a museum in the shadow of the Eiffel Tower. What she doesn't know is that one powerful man has a special reason to find the person responsible. Jack Harlan has all the money in the world, but it can't bring his brother back. His sibling was murdered during the theft of a scientific discovery that could have made the world a better place. Now, after a four-year search, Harlan learns that this bombing was the work of the same twisted man"--